Efficacy of immune‐checkpoint inhibitors in metastatic gastric or gastroesophageal junction adenocarcinoma by patient subgroups: A systematic review and meta‐analysis. (1st September 2020) - Kundel, Yulia; Sternschuss, Michal; Moore, Assaf; Perl, Gali; Brenner, Baruch; Goldvaser, Hadar
Abstract: Background: Efficacy of immune checkpoint inhibitors (ICIs) in metastatic gastric/gastroesophageal junction (GEJ) adenocarcinoma is inconsistent. Whether the efficacy of ICIs is comparable across different subgroups remains unknown. Methods: We identified randomized controlled trials (RCTs) that compared standard treatment for metastatic gastric/GEJ adenocarcinoma to ICIs. Hazard ratios (HRs) and 95% confidence intervals (CI) for overall survival (OS) were extracted and pooled in a meta‐analysis. Prespecified subgroups were included as follows: age at randomization (</≤65 vs ≥/>65 years), gender (female vs male), ethnicity (Asians vs non‐Asians), performance‐status (0 vs 1), tumor location (gastric vs GEJ), and histological subtype (diffuse vs others). OS in patients with programmed death ligand (PD‐L1) positive and with microsatellite instability‐high (MSI‐H) were also extracted and pooled in a meta‐analysis. Results: Five RCTs comprising 2, 264 patients were analyzed. Compared to standard therapy, ICIs did not improve OS (HR = 0.86, 95% CI 0.71‐1.03, P  = .10) and the effect of ICIs on OS was similar in all subgroups. Nonsignificantly greater effect sizes were seen in older patients (HR = 0.85 vs 0.88, P =  .81), male (HR = 0.82 vs 0.99, P  = .16), Asians (HR = 0.86 vs 0.96, P  = .55), performance‐status 0 (HR = 0.84 vs 0.88, P  = .81), GEJ tumors (HR = 0.78 vs 0.90, P  = .37), and nondiffuse subtype (HR = 0.71 vs 0.79, P  = .62). ICIs were associated with significantly improved OS in patients with MSI‐H (HR = 0.33, P  = .001), but not in PD‐L1 positive disease (HR = 0.86, P  = .06). Conclusions: Compared to standard treatment, ICIs in metastatic gastric/GEJ adenocarcinoma did not improve OS. None of the evaluated subgroups has shown increased magnitude of effect to ICIs, aside of the small group with MSI‐H tumors. Abstract : Compared to standard treatment, ICIs in metastatic gastric/GEJ adenocarcinoma did not improve OS. None of the evaluated subgroups including, age, gender, ethnicity, performance status, primary tumor location, and histological subtype, has shown increased magnitude of effect from ICIs. In exploratory analysis for small group with MSI‐H tumors, treatment with ICIs was associated with significant OS improvement compared to the control group.